A model to predict survival following pancreaticoduodenectomy for malignancy based on tumour site, stage and lymph node ratio. Issue 4 (April 2016) - Dasari, Bobby V.M.; Roberts, Keith J.; Hodson, James; Stevens, Lewis; Smith, Andrew M.; Hubscher, Stefan G.; Isaac, John; Muiesan, Paolo; Sutcliffe, Robert P.; Marudanayagam, Ravi; Mirza, Darius F.
Abstract: Background: Site of tumour origin, lymph node metastases and lymph node ratio (LNR) are identified as important factors determining prognosis in patients undergoing pancreaticoduodenectomy (PD). This study hypothesised that a prognostic index to predict survival could be developed through statistical modelling based on these pathological variables. Methods: Patients who underwent PD between 2004 and 2013 were included. Univariable and multivariable (Cox regression) analyses were performed to identify predictors of survival, and a prognostic index was derived. The prognostic index was then validated using an external patient cohort. Results: A total of 567 patients who underwent PD were used as a derivation cohort. Tumour site (p < 0.001), tumour size (p = 0.002), T-stage (p < 0.001), vascular involvement (p = 0.002), number of positive nodes (p < 0.001) and LNR (p < 0.001) were significantly associated with survival in univariable analysis. LNR (p < 0.001), tumour site (p < 0.001), T-stage (p = 0.007) remained significant predictors of survival in multivariable analysis, and were combined to derive a prognostic index. The accuracy of the prognostic index was assessed both on the original cohort, and a validation set of 194 patients from another institutional prospective database. The AUROC scores for predicting the overall survival at 3 years were 0.77 in the derivation cohort and 0.74 in the validation cohort. Conclusion: The Pancreaticoduodenectomy Prognostic Index is a validated clinico-pathological model based on tumour site, T-stage and LNR to predict long-term survival following PD.